Steam Reforming of Glycerol into Hydrogen Over Nano-Size Ni-Based Hydrotalcite-Like Catalysts - Hur, Eun; Moon, Dong Ju (AMER SCIENTIFIC PUBLISHERS, 2011)
Steam reforming (SR) of glycerol for the production of hydrogen was investigated over the nanosized Ni-based catalysts. The Ni-based catalysts were prepared by solid phase crystallization and impregnation methods, and characterized by N(2) physisorption, CO chemisorption, XRD, SEM, and TEM techniques. The Ni/gamma-Al(2)O(3) catalyst showed higher conversion and H(2) selectivity. However, it was slowly deactivated due to the carbon formation on the surface of catalyst and the sintering. It was found that the Ni based hydrotalcite-like catalyst (spc-Ni/MgAl) showed higher catalytic activity to prevent carbon formation than Ni/gamma-Al(2)O(3) catalyst in the SR of glycerol.